Penyuluhan Pencegahan Tuberkulosis untuk Meminimalisasi Penularan pada Masyarakat Lanjut Usia di Kabupaten Serdang Bedagai - Dicky Yuswardi Wiratma; Tiara Rajagukguk (University of Merdeka Malang, 2020)
Pulmonary tuberculosis is one of the highest prevalence of infectious diseases in the world. More than 90% of TB cases and deaths come from developing countries, one of which is Indonesia. The village of Tanjung Harap in Serdang Bedagai Regency still has a high rate of tuberculosis in the elderly. This can occur because of the low awareness of healthy living and knowledge about pulmonary tuberculosis. This counseling activity is intended so that the community, especially the elderly, know the dangers of pulmonary TB infectious diseases and know the precautions and when symptoms have arisen. Counseling was carried out by means of questionnaires, lectures, and video screenings about prevention and what actions should be taken as prevention of infectious diseases, especially pulmonary tuberculosis, this activity ends with blood pressure checks and vital signs. The results of this counseling showed a positive impact and increased knowledge to protect themselves and prevent the transmission of pulmonary tuberculosis in the elderly. Based on the results of the activities carried out, it can be concluded that this has an influence on the insight, knowledge and concern of the community, especially the elderly who are in the village of Tanjung Harap Serdang Bedagai Regency.DOI: https://doi.org/10.26905/abdimas.v5i3.4227